URBANISASI, MODERNISASI DAN PERUBAHAN SOSIAL PADA KOMUNITAS LOKAL PERKOTAAN: KASUS KOTA BARU METRO TANJUNG BUNGA, MAKASSAR - Batara Surya (TATALOKA, 2012)
This study aims to analyze the spatial physical changes in working as a determinant of social formation changes, processes of social interaction and social adaptation between migrants and local communities in new social formations and consequences of changes in social structure, social processes and cultural patterns of local communities in the Metro Tanjung Bunga area interest. Spatial physical changes take very quickly encourage the acceleration of development and modernization in the Metro Tanjung Bunga area. Working differentiation push social interaction processes between local communities and settlers in new social formations and within the framework to build social relationships and social relations that are integrative towards the fulfillment of basic needs and efforts to maintain the existence, so conditions of social change on local communities. The consequences of social change on local communities is changing of stratification system from simple stratification then evolved toward sharpening of economic stratification and cultural change from traditional agrarian to urban industrial.